Association of dysautonomia and different risk factors in patients with Guillain-Barré syndrome in a tertiary hospital in the Philippines - Gerald T. Pagaling; Lowrence Precious C. Dichoso; Nikolai Gil D. Reyes; Mario B. Prado (BMC Neurology)
Abstract Background Guillain-Barré syndrome (GBS) presents with progressive ascending weakness, but it can also present with dysautonomia such as tachycardia, blood pressure fluctuations, diaphoresis, ileus, and urinary retention. GBS patients with dysautonomia was observed to have longer hospital stays and higher mortality rates than those without dysautonomia. We aimed to determine the risk factors for dysautonomia and its manifestations among patients with GBS and compared their features to those without dysautonomia. Methods We conducted a 10 year-retrospective review of GBS patients admitted at the Philippine General Hospital. The patient demographics, comorbidities, GBS disability status scale (GBS-DS), GBS variants, parameters of dysautonomia, treatment, and outcome were recorded and analyzed. Simple and multiple logistic regression analysis were conducted to determine the factors associated with dysautonomia and the relationships were expressed using odds ratio. Results 71 patients were included, and 49% developed dysautonomia. Hypertension and tachycardia were the most prominent manifestations. There was an increase in the odds of developing dysautonomia in a one-year increase in age (OR: 1.11, p = 0.001) and a point increase in GBS-DS (OR:1.65, p = 0.037) during admission. Pre-morbid hypertension (OR:0.13, p = 0.028) and alcoholism (OR: 0.17, p = 0.037) are shown to decrease the odds of developing dysautonomia. Although GBS patients with dysautonomia had longer hospital stay (12.33 days), it only predicts 5.5% of the variability. Discussions The prevalence of cardiovascular manifestations was postulated from cardiosympathetic hyperactivity between arterial baroreceptors, cardiac parasympathetic fibers, and preganglionic sympathetic vasomotor fibers. The protective mechanism of premorbid hypertension could be attributed to the prior intake of antihypertensive medications, which mitigate cardiosympathetic fluctuations, while the protective effect of alcoholism needs to be further studied. Conclusion Patients who are older and with a high GBS-DS on admission, prompt close monitoring for the development of dysautonomia. The protective effects of premorbid hypertension and alcoholism needs further evaluation. The odds of developing pneumonia and being on a mechanical ventilator, while not statistically significant, could contribute to longer hospital stay of patients with dysautonomia. A larger prospective study is warranted to confirm these results.